Efficacy and safety of high-dose influenza vaccine in elderly adults: A systematic review and meta-analysis. Issue 21 (15th May 2017) - Wilkinson, Krista; Wei, Yichun; Szwajcer, Andrea; Rabbani, Rasheda; Zarychanski, Ryan; Abou-Setta, Ahmed M.; Mahmud, Salaheddin M.
Highlights: A comparative efficacy meta-analysis of high and standard dose influenza vaccines in the elderly. Two trials showed the high-dose vaccine was associated with lower rates of influenza infection. No evidence for clinically-relevant outcomes (influenza-associated hospitalizations and deaths). Pragmatic trials will be needed to determine if superiority persists in real-world settings. Abstract: Introduction: Older adults are prioritized for influenza vaccination but also have lowered antibody responses to the vaccine. Higher-doses of influenza antigen may increase immune response and thus be more effective. Our objectives were to compare the efficacy and safety of the high-dose influenza vaccine to the standard-dose influenza vaccine in the elderly (age > 65). Methods: Data sources : Randomized trials (RCTs) from Medline (Ovid), EMBASE (Ovid), Cochrane Library (Wiley), ClinicalTrials.gov, reference lists of relevant articles, and gray literature. Study selection : Two reviewers independently identified RCTs comparing high-dose influenza vaccine (60 μg of hemagglutinin per strain) to standard-dose influenza vaccine (15 μg of hemagglutinin per strain) in adults over the age of 65 years. Data extraction : Two reviewers independently extracted trial-level data including population characteristics, interventions, outcomes, and funding sources. Risk of bias was assessed using the Cochrane Risk of Bias tool. Results: We included seven eligible trials; all were categorized as having a low ( n = 3) or unclear ( n = 4) risk of bias. Patients receiving the high-dose vaccine had significantly less risk of developing laboratory-confirmed influenza infections (Relative Risk 0.76, 95%CI 0.65 to 0.90; I 2 0%, 2 trials, 41, 141 patients). Post-vaccination geometric mean titres and seroprotection rates were also higher in high-dose vaccine recipients. There were no protocol-defined serious adverse events in the included trials in either group. Conclusions: In elderly adults, the high-dose influenza vaccine was well-tolerated, more immunogenic, and more efficacious in preventing influenza infections than the standard-dose vaccine. Further pragmatic trials are needed to determine if the higher efficacy translates into higher vaccine effectiveness in adults over the age of 65.